Critical Insights into the Fantastic World of Mervyn Peake’s Gormenghast Trilogy - Jakovljević, Mladen M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Genre eclecticism, stylistic versatility and fertility, abundance of details, and temporal and spatial ambiguity centred around Gormenghast Castle, an immense architectural collage that has been home to seventy-seven generations of the Groan dynasty and a variety of other curiously grotesque inhabitants, make Peake’s Gormenghast trilogy a unique work of literature that defies standard literary classifications. Epistemological and ontological dilemmas about the nature of the fictional world and its interpretation as fantastic can be analysed by viewing its particularities within the frame of the author’s principles of worldbuilding, previous studies of Gormenghast, and more widely, within the context of its position in the domain of the fantastic. The individual elements of the work are not typically fantastic; however, the observance of their interrelations, as well as of the entire fictional reality from micro- and macro-perspective, reveals how Gormenghast and its world are shaped.